Evaluating the effects of electrokinetic stabilization variables on Atterberg limits and shear strength of clay soil using Taguchi method - Darmiyanti, Lydia; Munawir, As’ad; Rachmansyah, Arief; Zaika, Yulvi; Andi Suryo, Eko (Eastern-European Journal of Enterprise Technologies, 2025)
Clay soil often poses a significant challenge in construction projects due to its plasticity, low bearing capacity, and tendency to shrink or expand as moisture levels change. The properties and characteristics of clay soil make it have a low bearing capacity. Electrokinetic stabilization is an effective technique to overcome this clay soil problem. Previous research has identified the variables that influence electrokinetic stabilization, namely the voltage applied, the electrokinetic application time, the type of solution, the pH solution concentration, and the drying of the soil after electrokinetic stabilization. Of all the variables that influence electrokinetic stabilization, it is known that it can increase the Atterberg limit value and the bearing capacity (qu). This study aims to determine the percentage contribution of each variable to the increase in IP and qu values. A Taguchi experimental design was used to determine the contribution of each electrokinetic stabilization variable to the IP and qu values. The variables used in this study were solution concentration, voltage, electrokinetic duration, and curing time. The experiment was carried out by identifying the soil, determining the control and input factors based on the L27 orthogonal matrix, performing electrokinetic stabilization, testing the Atterberg limits and unconfined compressive strength, and analyzing the effect of each variable using statistical analysis. The results showed that the most influential variables in increasing the bearing capacity of the soil (qu) were the duration of the electrokinetic application, the voltage applied, and the concentration of the solution used. The most influential variable in increasing the qu value is the duration of electrokinetic application, which is 66.9 %; then the concentration of the solution is 29.72 %, and the voltage applied is 16.91 %. The treatment duration variable has no effect on increasing the qu value. From the results of this study, the application in the field in electrokinetic stabilization for clay soil needs to be considered for the duration of application, voltage, and concentration of the solution used so that there is optimum soil improvement